A deep insight on the correlation between slag viscosity fluctuation and decomposition of sulfur-bearing minerals in the entrained flow gasifier. (1st April 2020) - Shen, Zhongjie; Zhou, Jie; Liu, Xia; Liang, Qinfeng; Liu, Haifeng
Abstract: The fluctuation behavior of the coal slag viscosity in an entrained flow gasifier will increase the instability of the slag discharge and cause a blockage issue on the slag hole. The current research work gave a deep insight about the correlation between on the viscosity fluctuating behavior and the decomposition of the sulfur-bearing minerals in the coal slag. The measured viscosity-temperature curves of four coal slags with different sulfur contents showed different fluctuation behavior, ranging from 1200 to 1400 °C. Comparing to the fitting viscosity curve, the viscosity fluctuating difference and frequency increased with the increasing released gas volume, verified with a simulation experiment with malt syrup and argon. The decomposition and reaction of anhydride and CO was found to be critical to cause the bubble formation with the main gas phase of sulfur oxide inside. The capillary number (Ca) of the slag with bubbles was calculated and compared to the relative viscosity. Theoretical analysis showed a reverse tendency between the capillary number and relative viscosity of the slag, meaning the formation and deformation of bubbles during the slag transformation at high temperature and viscosity measurement process would cause the viscosity fluctuating behavior. Highlights: Decomposition or reaction of sulfur-bearing minerals caused the bubble formation. Both fluctuating amplitude and frequency increased with gas volume in slag. Relative viscosity displayed a reverse tendency with the capillary number. The increasing volume and deformation of bubbles lead to the viscosity fluctuation.